License to Play : The Ludic in Japanese Culture - Daliot-Bul, Michal (Book collections on Project MUSE., 2014)
"Play is one of the most powerful cultural forces in contemporary Japan and in other late modern societies. In this notable contribution to our understanding of play, Michal Daliot-Bul explores the intricate and dynamic transformations of culture and play (asobi) in Japan. Along the way, she takes readers on a theoretically informed journey to better comprehend what makes play a significant cultural function, asking such questions as "How can we explain the dialectics between play as a biological instinct and play as a culturally specific activity? What defines the best player? How is creativity related to play? What is the difference between play and playfulness? Are some cultures more play-oriented than others, and if so, why?" Daliot-Bul argues that the cultural meaning of play and its influence on sociocultural life are not inherent properties of a fixed, universal behavior called play but rather are conditioned by changing cultural contexts and competing social ideologies. Spanning Japan's premodern period to the twenty-first century, the extent and expressions of play described in this book become thought-provoking lenses through which to view Japanese social dynamics and cultural complexities. As she approaches the post-industrialized 1970s in Japan, Daliot-Bul's narrative also explores urban consumer culture as a system for organizing daily life, the tension between institutional and contemporary popular cultures, the production of new gender identities, and the cultural construction of urban space."--Publisher's description